Monthly migraine days, tablet utilization, and quality of life associated with Rimegepant – post hoc results from an open label safety study (BHV3000–201) - Johnston, Karissa; Harris, Linda; Powell, Lauren; Popoff, Evan; Coric, Vladimir; L’Italien, Gilbert; Schreiber, Curtis P. (Journal of headache and pain, 2022)
Background The objective of this study was to describe patterns in monthly migraine days (MMD) and tablet utilization, and to estimate health-related quality of life (HRQoL) measures in patients treated as needed (PRN) with rimegepant 75 mg over 52-weeks. Methods Eligible subjects were adults with ≥1 year history of migraine and ≥ 6 MMD at baseline, who used rimegepant 75 mg up to once daily PRN (at their discretion) for up to 52-weeks in an open-label safety study (BHV3000–201; NCT03266588). Mean MMD were calculated at each 4-week period, along with mean monthly tablets taken. Migraine-specific quality of life (MSQv2) data were mapped to EQ-5D utilities and used to characterize HRQoL over time. A published network meta-analysis was used to characterize pain hours as well as time periods spent migraine free. Results One thousand forty four subjects were included in this post-hoc analysis. Overall mean MMD were 10.9 at baseline and decreased to 8.9 by week 52. Tablet use remained stable over the follow-up period. A total of 0.08 incremental QALYs were associated with rimegepant use. Conclusion For subjects with 6 or more MMD, acute treatment of migraine attacks with rimegepant 75 mg on a PRN basis over one-year of follow-up was found to be associated with reduced MMD frequency without an increase in monthly tablet utilization, and improved HRQoL. There was no evidence of medication-related increases in MMDs when rimegepant 75 mg was used as needed for the acute treatment of migraine over 52-weeks. Trial registration ClinicalTrials.gov identifier NCT03266588 .